Biomechanical analysis of the lower limb segments in the load carriage dynamics of Malaysian primary school children walking performance - Azmin Sham, Rambely (Universiti Malaysia Perlis (UniMAP), 2014)
National Symposium on Advancements in Ergonomics and Safety (ERGOSYM2009), 1st – 2nd December 2009, Perlis, Malaysia